Effect of Protein and Energy-Dense Nutritional Supplement with Immunonutrients on Cachexia in Cancer Patients: An Open-Label, Single-Arm Study Among Indian Patients - Rachana Bhoite; Varalakshmi Lalithya Pratti; Vinita Satyavrat; Rahul Rathod (International Journal of Nutrition, 2023)
Background Cachexia is highly prevalent in cancer patients and is responsible for as much as 20% of all cancer deaths. Nevertheless, there is little emphasis on cachexia in routine clinical practice. This study looks at the efficacy and tolerability of a protein and energy-dense nutritional supplement with immunonutrients on cachexia in cancer patients. Methods This was a three-month, prospective, open-label study of patients undergoing radiotherapy and/or chemotherapy for head and neck or gastrointestinal or lung cancer. Efficacy endpoints were mean change in muscle strength, acute phase proteins (albumin and pre-albumin), C-reactive protein (CRP) levels, weight, Glasgow prognostic score (GPS), and nutritional status at the end of the study period. Results The study population consists of 47 (79.66%) males and 12 (20.34%) females with a mean age of 47.98 ± 12.16 years. The mean change in muscle strength, albumin, pre-albumin, CRP levels, and weight for the overall study population was 0.17 ± 12.09 kg (P=0.9145), -0.05 ± 0.53 g/dl, (P=0.5888), -0.01 ± 0.09 g/dl (P=0.2951), 0.50 ± 37.41 mg/dl (P=0.9258), -0.59 ± 3.70 kg (P=0.2265), respectively. At the end of the study period, there was a significant improvement in the nutritional status concerning total calories, protein, and fat intake. Conclusion Protein and energy-dense nutritional supplement with immunonutrients might help in the improvement of muscle strength, GPS, and dietary intake. The addition of the supplement to the diet regime of patients with cancer cachexia increases their daily consumption of proteins which might translate to multimodal clinical benefits.
Keywords: Cachexia